PENGARUH LATIHAN FOOT DRIBBLE TERHADAP KETERAMPILAN MENGGIRING BOLA PADA SSB PCSS U-15 PEKANBARU - Fadhli, Muhammad; ', Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract:: As for the problem is based on observations in doing researchers in the field batrai-p on SSB PCSS Pekanbar, researchers found flaws in the ball dribbling at the time of the trial or official competition, While the ball dribbling away from the control of the foot so that the ball easily grab the opponent, conditions so would be detrimental to the team. Errors that occurred while dribbling one factor contributing to her is the players have not mastered the techniques the ball dribbling is good and right. So it is not able to demonstrate achievement of the maximum for the team. The purpose of this study to determine the effect of exercise on Foot Dribble for skills at SSB PCSS U-15 Pekanbaru. The kind of this research is an experiment to see the influence of forms of exercise. In this study researchers took population SSB PCSS U-15 Pekanbaru PCSS U-15 sum 16 people. Base this data is used completely population to become xample. Base this date has found from pre-test and post-test. Instrument has done research is test. Soccer dribble test as instrument to measure dribble skill. Analysis has done the used test. Based on analysis data and discussio, as evidenced by thitung 12,326 and ttabel 1,753. Means thitung> ttabel At some level ɑ = 0.05. then can be concluded that there is significant influence from foot dribble to improve the skills of dribble on SSB PCSS U-15 Pekanbaru.Key Words: Exercise Foot Dribble, Dribble, soccer